Immediate ecotoxicological effects of short-lived oil spills on marine biota - Corina P. D. Brussaard (Nature Portfolio, 2016)
Large oil spills have negative effects on marine ecosystems, but the effects of chronic smallscale spills are less well understood. Here, Brussaard et al. detect high bioavailability and toxicity of small-scale crude oil spills within 24 hours after release, which are associated with localised declines in marine plankton.